2021
DOI: 10.35848/1882-0786/abd5cc
|View full text |Cite
|
Sign up to set email alerts
|

Tunable high-order harmonic and dual-wavelength mode-locking in Er-doped fiber laser based on Ti3C2T x -Mxene

Abstract: We demonstrate an all fiber high-repetition-rate erbium-doped ultrashort laser based on the Ti3C2T x -Mxene saturable absorber (SA), and the 56th harmonic mode-locking with a repetition rate of 622.2 MHz, a central wavelength of 1590.7 nm, and a pulse duration of 1.31 ps is achieved. Meanwhile, dual-wavelength mode-locking pulses are also realized, with the central wavelengths of 1575.6, 1587.5 nm. The results of the work indicate that Ti3C2T x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…[59][60][61][62][63] Through sonication exfoliation of multilayered MXenes, few-layered MXenes were obtained. [64][65][66] A suitable liquid medium is the key factor to obtain efficient exfoliation and stable dispersion of 2DLMs. Hernandez et al reported that the surface energy or surface tension of solvents needs to match that of the materials, so as to achieve effective exfoliation with a minimal energetic cost.…”
Section: Top-down Exfoliation To Prepare 2dlmsmentioning
confidence: 99%
See 2 more Smart Citations
“…[59][60][61][62][63] Through sonication exfoliation of multilayered MXenes, few-layered MXenes were obtained. [64][65][66] A suitable liquid medium is the key factor to obtain efficient exfoliation and stable dispersion of 2DLMs. Hernandez et al reported that the surface energy or surface tension of solvents needs to match that of the materials, so as to achieve effective exfoliation with a minimal energetic cost.…”
Section: Top-down Exfoliation To Prepare 2dlmsmentioning
confidence: 99%
“…Ti 3 C 2 T x is the most studied MXene material for achieving the ultra-short pulses in passively mode-locked fiber lasers. 64,220,[301][302][303][304][305][306][307] Other MXenes such as V 2 CT x , [308][309][310] Ti 2 CT x , 311 Ta 2 CT x , 312 Nb 2 C, 65 Mo 2 C, 313 and Ta 4 C 3 314,315 were also employed as the SAs for ultra-short pulsed fiber laser generation. Up to now, by using MXenes as the SA, the wavelength of the obtained pulsed laser in passively mode-locked fiber lasers spans from about 1031.5 nm 316 to 1891.82 nm.…”
Section: Passively Mode-locked Fiber Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the aforementioned three microfiber structures, there is also a rather simpler method to form the SA by sandwiching the SA material such as Ti 3 C 2 T x between two fiber ferrules as depicted in Figure 7d. [ 131 ] The Ti 3 C 2 T x was processed into a composite film by mixing 10 mL Ti 3 C 2 T x supernatant with 10 mL of PVA solution, which was treated by ultrasonication for 24 h. The Ti 3 C 2 T x /PVA composite film was cut into 1 × 1 mm 2 size and placed in between two fiber ferrules to form the SA. In comparison to the microfiber based SAs, the fiber ferrule structure is simpler for handling and operation, while at the expense of shorter interaction length and lower optical damage threshold due to the physical contact between the SA materials and the fiber ferrules.…”
Section: Saturable Absorbers Based On Mxenesmentioning
confidence: 99%
“…d) Fiber ferrules. Reproduced with permission [131]. Copyright 2021, The Japan Society of Applied Physics.…”
mentioning
confidence: 99%